The scream of sins - Nickson, Chris (Nickson, Chris. Simon Westow mysteries, 2024)
"Leeds, October 1824. Thief-taker Simon Westow's job seems straightforward. Captain Holcomb's maid, Sophie, has stolen important papers that could ruin the family's reputation, and he's desperate for their return. But the case very quickly takes a murderous turn, and it becomes clear the papers are hiding a host of sins . . . During the search, Simon's assistant, Jane, hears a horrific tale: men are snatching young girls from small towns for use by the rich. Those who are unwanted are tossed on to the streets of Leeds to survive among the homeless. With the help of an unlikely, deadly new companion, Jane will do everything to discover who's responsible and make them pay. Can Simon and Jane recover Holcomb's letters and get justice for the stolen girls? It becomes a battle that might result in them losing everything . . . including their lives."-- Book jacket.